2016
DOI: 10.1088/1748-6041/11/1/015014
|View full text |Cite
|
Sign up to set email alerts
|

Selective cell adhesion on femtosecond laser-microstructured polydimethylsiloxane

Abstract: We show that femtosecond laser irradiation of polydimethylsiloxane (PDMS) enables selective and patterned cell growth by altering the wetting properties of the surface associated with chemical and/or topographical changes. In the low pulse energy regime, the surface becomes less hydrophobic and exhibits a low water contact angle compared to the pristine material. X-ray photoelectron spectroscopy (XPS) also reveals an increased oxygen content in the irradiated regions, to which the C2C12 cells and rabbit anti-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…Both the matrix stiffness and nanoscale spatial organization of the ligands direct stem cell fate (Engler et al, 2004, 2006; Harris et al, 2013; Muth et al, 2013; Amschler et al, 2014; Ye et al, 2015). The physical cues are not restricted to elasticity; local changes in surface structure, hydrophobicity, roughness, and charge density lead to different cell adhesion and proliferation properties (Kiroshka et al, 2014; Alshehri et al, 2016; Pedraz et al, 2016). Taken together, there is an integrated response to external and internal stimuli on the nanoscale, both physical and biochemical in nature (Wickström and Niessen, 2018) (Figure 1).…”
Section: Cellular Attachment At the Nanoscalementioning
confidence: 99%
“…Both the matrix stiffness and nanoscale spatial organization of the ligands direct stem cell fate (Engler et al, 2004, 2006; Harris et al, 2013; Muth et al, 2013; Amschler et al, 2014; Ye et al, 2015). The physical cues are not restricted to elasticity; local changes in surface structure, hydrophobicity, roughness, and charge density lead to different cell adhesion and proliferation properties (Kiroshka et al, 2014; Alshehri et al, 2016; Pedraz et al, 2016). Taken together, there is an integrated response to external and internal stimuli on the nanoscale, both physical and biochemical in nature (Wickström and Niessen, 2018) (Figure 1).…”
Section: Cellular Attachment At the Nanoscalementioning
confidence: 99%
“…A fundamental understanding of the nanoscale details of cellular environments is essential for the structural and functional design of biomaterials that can mimic the natural cellular milieu (Hickey and Pelling 2019). Physical properties, such as elasticity, hydrophobicity, roughness, and charge density, cause different cell adhesion and proliferation properties (Kiroshka et al 2014;Alshehri et al 2016;Pedraz et al 2016). Engler et al (2006) reported that the stiffness of the substrate directed the differentiation of stem cells; that is, hardness and softness regulated the fate of the stem cells, although none of the components was a biological material.…”
Section: Biomedical Applicationsmentioning
confidence: 99%
“…35,36 For electrospun scaffolds all above mentioned properties can be adjusted during manufacturing, avoiding additional postprocessing steps, which makes them a great candidate for tissue engineering. [37][38][39] Piezoelectric materials modulate cellular behavior via surface charges generated in response to cellular interaction and vibration stimulus. 32 In vivo studies have shown increased cell activity for PVDF scaffolds implanted in rats.…”
Section: Introductionmentioning
confidence: 99%